Electroanalysis of single nanoparticles via particle-electrode collision processes - Zhou, Y (2012)
This thesis begins with the investigation of size- and density-effects of AgNP arrays in voltammetry, including the study of size-dependent adsorption behavior by observing thallium underpotential deposition on AgNPs, and surface coverage eects of AgNP modified electrodes in voltammetry showing the transition from convergent to linear diffusion. The main focus of this thesis is next presented: the electroanalysis of nanoparticles (NPs) studied via their impacts with an electrode via both indirect (i:e: electrocatalytic) and direct electrochemical measurements. The study first realises the direct detection and sizing of silver NPs (AgNPs) using anodic particle coulometry (APC). This theme is then extended to gold and nickel NPs, aggregation studies and the measurement of sticking coecients. Furthermore, the determination of nanoparticle concentration is realised by measurement of the flux to electrodes. In contrast to APC, electrode-particle impacts using surface tagged NPs provide a non-destructive way of sizing the NPs from the charge associated with one monolayer of "tag". In addition to tagged NPs, underpotential deposition and bulk deposition of metal onto single AgNPs are also observed as part of the studies of indirect electrochemical measurement. Finally the charge transfer kinetics of the oxidation of silver and nickel nanoparticles is studied.